Analisis Biaya Akibat Sakit serta Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 dengan Penyakit Jantung - Sari, Lusiani Septika (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Indonesia is the fourth most deaths due diabetes mellitus and heart disease among south Asia countries. Cost of illness from diabetes mellitus with heart disease is the highest cost if it is compared with combination of diabetes mellitus with other chronic disease. This study with 110 patients as samples is aiming to describing the cost of illness and quality of life of patients with type 2 diabetes mellitus with heart disease in X public hospital. With cross sectional research design, primary data is collected with survey technique that uses structured questionnaire and secondary data is obtained through medical record document review along with another supporting document. This research has been done from March until May in 2014. The population is all type 2 diabetes mellitus patient with heart disease who was doing in-patient visit in X Bengkulu, the number of sample was 110 patients. The annual cost of illness due to type 2 diabetes mellitus with heart disease per patient was Rp. 6,081,572, with direct cost is reached (81.54%) and indirect cost (18.46%). The largest proportion of the cost was drug (37.05%). Factors that affect COI were Length of Stay (LOS) and the type of work, and factor affect quality of life was duration of illness. It is recommended that X Public Hospital Bengkulu should prepare clinical pathways and hospital formulary. The central government needs to revise national formulary with considering variability of country situation and develop program to improve quality of DM patient.